Analisis Dampak Keberadaan Perusahaan terhadap Kehidupan Sosial Ekonomi Masyarakat Desa Paya Pinang - Husna Sari Siregar; Salsabila Lubis; Nazwa Athaya Aldi; Dinda Arifah; Ahmad Baihaqi (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
This study aims to analyze the impact of the existence of a company on the social and economic life of the community in Paya Pinang Village. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation during the implementation of the 2026 Community Service Program (KKN) of UIN Sumatera Utara. Informants were selected using purposive sampling, involving residents, company employees, retired employees, and community leaders who possessed relevant knowledge and experience regarding the company’s presence. The results show that the company has a positive impact on the economic conditions of the community, particularly through the provision of employment opportunities, more stable income, housing facilities, allowances, bonuses, and old-age benefits. The company also provides opportunities for residents to develop side businesses and contributes to social activities and Corporate Social Responsibility (CSR) programs. From a social perspective, relationships among residents generally remain harmonious, and the company’s presence does not create significant conflicts. However, several needs remain, including improvements to residential facilities, provision of productive business locations, and enhancement of community empowerment programs. The data were analyzed through data reduction, data presentation, and conclusion drawing, supported by source triangulation.